Big Five Personality Traits of Extraversion and Neuroticism, and Risky Driving Behavior of Malaysian Drivers - Rosli, Nur Shazwani (Journal of Techno-Social, 2025)
Majority of traffic accidents had human involvement, and attitudes that contributed to risky driving behavior were impacted by personality traits. Few research, however, have looked at each Big 5 Personality’s impact on risky driving behavior separately. Furthermore, the results on extraversion and neuroticism as the Big 5 Personality characteristics of their predictive usefulness were conflicting and ambiguous. The purpose of this study is to determine how extraversion and neuroticism affect the ability of Malaysian highway drivers to predict risky driving behavior. The study employed a quantitative survey method, and 311 usable questionnaires were collected from the motorists using the highway intercept techniques. Partial Least Squares (PLS) path modelling was used in the data analysis. Risky driving behavior was found to be positively and significantly correlated with extraversion and neuroticism. These findings provided an empirical basis to develop evidence-based road safety measures on the personality traits of motorcar drivers. To increase traffic and road safety, it is crucial to be able to recognise and anticipate the characteristics of risky driving in human behavior.